Terrestrial site fidelity of maternal polar bears in western Hudson Bay - Natasha J. Klappstein; David McGeachy; Nicholas W. Pilfold; Nicholas J. Lunn; Andrew E. Derocher (Arctic Science)
Seasonal migrations allow access to temporally varying resources and individuals may show fidelity to specific locations, particularly for important life processes such as reproduction. Polar bears (Ursus maritimus) are a sea ice-dependent species that migrate between marine and terrestrial habitats, the latter being important for parturition and early cub rearing. However, fidelity to maternity dens is poorly understood. Using capture and telemetry data collected between 1979 and 2018, we assessed site fidelity of female polar bears in the Western Hudson Bay subpopulation in Manitoba, Canada. We compared within-individual inter-year distances between dens to between-individual distances via non-parametric bootstrapping, and used generalized additive models to assess how maternal age, years between denning events, and sea ice conditions affected fidelity. Within-individual distances were smaller than between-individual distances by approximately 18.7 km, indicating some evidence of fidelity. Inter-den distances increased with time between denning events, but no other variables significantly affected fidelity. Our findings suggest that western Hudson Bay polar bears may exhibit fidelity to areas within the larger denning region, but not to specific dens. Understanding the site fidelity of maternal polar bears has important implications for population dynamics, on-land spatial distributions, and conservation efforts aimed at preserving important habitat for reproduction.